Microalgae growth in ultra-thin steady-state continuous photobioreactors: assessing self-shading effects - Saccardo, Alberto; Bezzo, Fabrizio; Sforza, Eleonora (Frontiers in Bioengineering and Biotechnology, 2022)
To disclosure the net effect of light on microalgal growth in photobioreactors, self-shading and mixing induced light-dark cycles must be minimized and discerned by the transient phenomena of acclimation. In this work we performed experiments of continuous microalgal cultivation in small scale photobioreactors with different thickness (from 2 mm to 35 mm): working at steady state allowed to describe the effect of light after acclimation, while the geometry of the reactor was adjusted to find the threshold light path able to discriminate different phenomena. Experiments showed an increased inhibition under smaller culture light paths, suggesting a strong shading effect at thicknesses higher than 8 mm where mixing induced light-dark cycles may occur. A Haldane-like model was applied and kinetic parameters retrieved, showing possible issues in the scalability of experimental results at different light paths if mixing induced light-dark cycles are not considered. To further highlight the influence of mixing cycles, we propose an analogy between small scale operations with continuous light and PBRs operations with pulsed light, with the computation of characteristic parameters from pulsed light microalgae growth mathematical modeling.